IMPROVING FISH POND WATER QUALITY THROUGH CLAY-FILTRATION AND BIOLOGICAL TREATMENT METHOD - Umudi, Ese Queen; Umudi, Ogheneyoma Peter; Asabor, B. M.; Igere, Okeoghene Festus (FUDMA JOURNAL OF SCIENCES, 2024)
This study sought to evaluate the physical, chemical and bacterial parameters of fish pond wastewater after treatment using clay filtration and biological treatment methods. Appropriate parameters were analyzed in other to determine the quality of the wastewater before and after treatment with clay, using standard methods. The clay sample used, which was obtained from Ossiomo Edo State was also analyzed by measuring its mineralogical and geochemical composition using x-ray diffractometer and atomic absorption spectrophotometer respectively. The clay was found to be composed mainly of kaolinite and alumino-silicates. From the result obtained from the treatment of the fish pond wastewater showed significant percentage reduction in the relevant pollution parameters (electrical conductivity - 54.39% reduction, biochemical oxygen demand - 95.94% reduction, total dissolved solids - 40.25% reduction, chloride - 89.40% reduction, ammonia-nitrogen - 92.27% reduction, phosphate - 23.24% reduction, turbidity 94.11% reduction, total bacteria count - 92.57% reduction). The values obtained after treatment were lower than WHO and FEPA limit values and favoured quality production of fish and other non-potable usage, indicating that clay filtration is a cost-effective and eco-friendly method which can be employed in the treatment of fish pond wastewater.